Analisis Kinerja Keuangan Dan Kemampuan Keuangan Pemerintah Daerah Dalam Pelaksanaan Otonomi Daerah di Kabupaten Barito Kuala Tahun 2015-2018 - Sri Wardani; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study aims to assess the financial performance of the local government of Barito Kuala Regency by using the Financial Ratio Analysis of the Regional Budget and Revenue (APBD) of Barito Kuala Regency in the 2015-2018 Fiscal Year. In this study, the analysis tools used are Regional Financial Performance Analysis and Analysis of Regional Financial Capabilities. Financial Performance Analysis is measured by calculating the Independence Ratio, Activity Ratio, Effectiveness and Efficiency Ratio, and Growth Ratio. At the same time, Financial Ability Analysis is measured by calculating the Routine Ability Index and Fiscal Autonomy Degree Ratio.Based on the results of the calculation of Regional Financial Performance, it can be concluded that the relationship pattern of regional independence is instructive, meaning that the provincial government is still very dependent on central government transfer funds. Simultaneously, the Activity Ratio level is not balanced, where local governments prioritize Indirect Expenditure compared to Direct Expenditure. However, the level of regional effectiveness and efficiency ratio shows a practical and efficient level. Based on the average growth ratio shows that growth is fluctuating from year to year. Change tends to be positive, but Direct Spending shows negative growth. While based on the results of the calculation of Regional Financial Capabilities, it can be concluded that the results of the analysis of Routine Capacity Index and Fiscal Autonomy Degree Ratio are on a scaling scale, meaning that the financial capacity of Barito Kuala district is not yet ideal, because the role of the central government is still very dominant